Online Monitoring and Analysis of Hydroabrasive Cutting by Vibration - Sergej Hloch; Alessandro Ruggiero (Advances in Mechanical Engineering, 2013)
The paper deals with the investigation of accompanying physical process, vibration, arising from the abrasive waterjet cutting of stainless steel. Samples of the square cross-section with the use of preplanned range of technological factors were cut. During the cutting of target material AISI 309 vibration by piezoelectrical accelerometers PCB IMI 607 A11 was recorded. The accelerometers were oriented perpendicular to the direction of the cut. Scanned data were processed through a virtual instrument created in LabVIEW 6.8. Sampling frequency of the recorded signal was 30 kHz. Investigated was development of the RMS value in particular frequencies. In order to confirm hypothetical assumptions about direct relation between vibration emission and surface quality, further experiment will be done. Current results are possible used for detection of defects during hydroabrasive cutting of materials, in case of focusing tube fracture, orifice damage in the cutting head, in case of fragile material cutting by means of controlled penetration.